2022
DOI: 10.2196/35898
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship Between Protein Intake in Each Traditional Meal and Physical Activity: Cross-sectional Study

Abstract: Background Protein intake plays an important role in the synthesis and maintenance of skeletal muscles for the prevention of health risks. It is also widely known that physical activity influences muscle function. However, no large-scale studies have examined the relationship between daily dietary habits, especially the timing of protein intake, and daily physical activity. Objective The purpose of this cross-sectional study was to investigate how prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…The general characteristics of the study group are indicated in Table 1. As described previously [28,29], the ratio of carbohydrate intake within the macronutrients in the current participants was lower than the Dietary Intake Standards for the Japanese, which is 50-65% carbohydrate in all ages. Interestingly, in a day, the carbohydrate ratio was higher at breakfast and lower at dinner.…”
Section: Basic Characteristicssupporting
confidence: 47%
“…The general characteristics of the study group are indicated in Table 1. As described previously [28,29], the ratio of carbohydrate intake within the macronutrients in the current participants was lower than the Dietary Intake Standards for the Japanese, which is 50-65% carbohydrate in all ages. Interestingly, in a day, the carbohydrate ratio was higher at breakfast and lower at dinner.…”
Section: Basic Characteristicssupporting
confidence: 47%
“…Konishi et al also showed that serum concentrations of triglycerides and SFA were significantly decreased in a group of participants with a high intake of fish oil at breakfast [19]. In addition, other studies have shown a better health status in people with a higher protein intake at breakfast [20]. In addition, the recent study by Truman et al showed that women whose breakfast, as opposed to lunch or dinner, contributed the greatest percentage to their daily fat intake had higher inflammatory marker levels compare to women whose dinner contributed the most to their fat intake [21].…”
Section: Introductionmentioning
confidence: 94%